2022
DOI: 10.1155/2022/2684474
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphisms, Dominions, and Various Classes of Saturated Semigroups

Abstract: In this paper, we discussed some saturated classes of ℋ -commutative semigroups, left (right) regular semigroups, medial semigroups, and paramedial semigroups. The results of this paper significantly extend the long standing result about normal bands that normal bands were saturated and, thus, significantly broaden the class of saturated semigroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a related direction, Ahanger et al [11] have established the saturation of generalized left [right] regular semigroups. Additionally, Alam et al [12] have identified some saturated classes of H-commutative, left [right] regular semigroups, medial semigroups, and paramedial semigroups Recently, in [13] the authors have identified several saturated classes of structurally regular semigroups. However, the complete identification of all saturated varieties of semigroups is an open problem.…”
Section: Theorem 5 ([6] (Theorem 54))mentioning
confidence: 99%
“…In a related direction, Ahanger et al [11] have established the saturation of generalized left [right] regular semigroups. Additionally, Alam et al [12] have identified some saturated classes of H-commutative, left [right] regular semigroups, medial semigroups, and paramedial semigroups Recently, in [13] the authors have identified several saturated classes of structurally regular semigroups. However, the complete identification of all saturated varieties of semigroups is an open problem.…”
Section: Theorem 5 ([6] (Theorem 54))mentioning
confidence: 99%